Legal Protection for Victims of Theft Crimes Who Take Independent Action: A Study of Justice for 'Victim-Offenders' - Rizky Septian; Fathurrahim Fathurrahim; Basto Daeng Robo; Sophian Y. Selajar; Arisa Murni Rada (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The purpose of this study is to analyze the legal provisions regarding the rights of victims of theft to defend themselves and their property, as well as to examine the legal protection mechanisms that can prevent secondary victimization of victims in the law enforcement process. This issue is important because in the practice of criminal justice in Indonesia, there are often situations where victims of theft who resist the perpetrator are potentially prosecuted if their actions cause harm to the perpetrator. This condition shows a paradox in the criminal justice system, where victims who should receive protection instead face the risk of criminalization as a result of their acts of self-defense. This raises issues of justice and has the potential to create secondary victimization of victims through a law enforcement process that is insensitive to the position of victims. Therefore, this research is urgent to examine in more depth how Indonesian criminal law regulates self-defense and how legal protection mechanisms can be developed so that victims are not further harmed in the criminal justice process. This study uses a normative-juridical research method with a legislative approach and a conceptual approach analyzed through systematic interpretation and legal content analysis of various relevant legal sources. The results of the study show that, normatively, Indonesian criminal law recognizes the concept of self-defense as a justification, but the existing regulations still leave room for broad interpretation, which has the potential to cause legal uncertainty for victims who resist perpetrators of theft. In addition, victim protection mechanisms in the law enforcement process have not been fully able to prevent secondary victimization. This study concludes that there is a need to strengthen the regulatory framework, develop law enforcement guidelines that are more sensitive to victims, and adopt an approach that is more oriented towards victim protection in the criminal justice system. The novelty of this study lies in its analysis, which places victims who engage in independent resistance as the main subject of study from the perspective of legal protection and the prevention of secondary victimization in Indonesian criminal law.